2009
DOI: 10.1177/0022022108328919
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Bidimensional Acculturation Scores

Abstract: Understanding score reliability is a necessary step in examining the validity of acculturation instruments. Thus, the authors evaluate the aggregate reliability of three multigroup, bidimensional acculturation instruments: General Ethnicity Questionnaire— Abridged, Stephenson Multigroup Acculturation Scale, and Vancouver Index of Acculturation. Reliability generalization techniques are used to analyze 51 internal consistency estimates and 6 sample characteristics for these instruments. Overall, reliability est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 37 publications
6
67
0
Order By: Relevance
“…The GEQ uses a 5-point Likert Scale (1 = strongly disagree, 5 = strongly agree). Good psychometric properties of the GEQ have been well documented (Huynh, Howell & Benet-Martinez, 2009;Tsai, Ying & Lee, 2000). The current study found the GEQ to have good internal consistency (α = .83).…”
Section: Covariate Measuressupporting
confidence: 60%
“…The GEQ uses a 5-point Likert Scale (1 = strongly disagree, 5 = strongly agree). Good psychometric properties of the GEQ have been well documented (Huynh, Howell & Benet-Martinez, 2009;Tsai, Ying & Lee, 2000). The current study found the GEQ to have good internal consistency (α = .83).…”
Section: Covariate Measuressupporting
confidence: 60%
“…Mainstream cultural orientation (VIA-M) was operationalized as scores on the VIA-FC subscale for participants attending a French-speaking university and as scores on the VIA-EC subscale for participants attending an English-speaking university. Past research has shown that the VIA is a valid and reliable cultural orientation questionnaire (Huynh, Howell, & Benet-Martínez, 2009;Ryder et al, 2000). Internal consistency in this sample was acceptable for both mainstream (Cronbach's αT1 = .77 for VIA-FC and αT1 = .76 for VIA-EC) and heritage (Cronbach's αT1 = .91) subscales.…”
Section: Methodsmentioning
confidence: 61%
“…Research on migrants' acculturation has shown consistent support for a bidimensional model across different mainstream and heritage cultures (Huynh, Howell, & Benet-Martínez, 2009). We therefore expected that the bidimensional structure of Locals' Bidimensional Acculturation Model would not vary across different contexts (UK, Germany, USA, China, and India; Hypothesis 1).…”
Section: Study 2 Dimensionality Of the Multi-via Beyond A Western Conmentioning
confidence: 95%